FairBase: a comprehensive database of fungal A-to-I RNA editing. (19th February 2019) - Liu, Jinding; Wang, Dongbo; Su, Yinna; Lang, Kun; Duan, Rongjing; Wu, YuFeng; Ma, Fei; Huang, Shuiqing
Abstract: Frequent A-to-I RNA editing has recently been identified in fungi despite the absence of recognizable homologues of metazoan ADARs ("Adenosine Deaminases Acting on RNA"). In particular, there is emerging evidence showing that A-to-I editing is involved in sexual reproduction of filamentous fungi. Here, we report on the creation of FairBase — af ungalA -to-I R NA editing database that provides a platform for deep exploration of fungal RNA editing to relevant academic communities. This database includes a comprehensive collection of A-to-I editing sites in six filamentous fungal species, together with extensive annotations for each editing site. In FairBase, users can conveniently search editing sites and obtain editing levels for each editing site in various RNA-seq samples. In addition, the pathways involving RNA editing are built in FairBase to help users understand the functions of RNA editing. Furthermore, each fungal species has a genome browser (JBrowse) that allows users to explore A-to-I editing in a genomic context. FairBase is the first fungal RNA editing database.